Validation Method of 3,4-Methylenedioxymethamphetamine (MDMA) Analysis Using Gas Chromatography Mass Spectroscopy - Muhammad Taufik; R.A. Fani Miranda; Andriayani Andriayani (Talenta Publisher, 2025)
MDMA is known as a narcotic and stimulant is a drug that is often abused, both in pill and powder form. Therefore, it is important to have an accurate and sensitive analysis method to detect the presence of MDMA especially in urine samples of drug users. In this work, optimization of the GC-MS method was carried out to obtain the best separation conditions and the highest sensitivity using the GCMS instrument. This study aims to develop a validation method for the analysis of 3,4-methylenedioxymethamphetamine (MDMA) using the Gas Chromatography-Mass Spectrometry (GCMS) technique. The results of the analysis showed that the accuracy, precision, linearity, limit of detection, limit of quantification and selectivity were respectively: 97.53%, 3.66%, R² ≥ 0.99, LOD 0.7 ppm, LOQ 2.35 ppm, and Rs 19.83. The results of the study showed that this method has good accuracy with acceptable precision values ​​and low enough LOD and LOQ to detect MDMA at appropriate concentrations. Thus, this validated GC-MS method can be effectively applied for the analysis of MDMA in various urine sample matrices, especially in the development of the field of analytical chemistry.